TLR4/TIRAP polymorphisms are associated with progression and survival of patients with symptomatic myeloma. (13th November 2015) - Bagratuni, Tina; Terpos, Evangelos; Eleutherakis‐Papaiakovou, Evangelos; Kalapanida, Despoina; Gavriatopoulou, Maria; Migkou, Magdalini; Liacos, Christine‐Ivy; Tasidou, Anna; Matsouka, Charis; Mparmparousi, Despoina; Dimopoulos, Meletios A.; Kastritis, Efstathios
Summary: Myeloma cells thrive in an environment of sustained inflammation, which impacts the development and evolution of the disease, as well as drug resistance. We evaluated the impact of genetic polymorphisms in the Toll‐like receptor 4 (TLR4) pathway, which have been implicated in different inflammatory responses in the outcomes of patients with symptomatic multiple myeloma (MM) who have received contemporary therapies. We found that the presence of single nucleotide polymorphisms (SNPs) in both the TLR4 and toll/interleukin‐1 receptor (TIR)‐associated protein ( TIRAP ) genes was associated with lower response to primary therapy mainly for patients who received immunomodulatory drugs but not in patients treated with bortezomib‐based therapies. Furthermore, TIRAP SNP was associated with a significantly shorter progression‐free survival and overall survival, independently of other prognostic factors, such as age, transplant, International Staging System stage, lactate dehydrogenase and cytogenetics. This is the first study to demonstrate the effect of SNPs in TLR4/TIRAP in MM. Our data indicate that genetic variability in the immune system may be associated with different responses to antimyeloma therapies and may be a critical component affecting the natural history of the disease, providing the basis for further investigation of the role of these pathways in myeloma.